Tissue specific role of ABCA1 in lung cholesterol homeostasis under high-cholesterol diet - Ma, Jian; Gong, Zhongwen; Lu, Hong; Yang, Han; Wang, Shengquan; Zhu, Qian; Liu, Hongya; Li, Yongjia; Zhang, Yuemei; Lian, Xuemei (Frontiers in Nutrition, 2025)
BackgroundATP-binding cassette subfamily A1 (ABCA1) and sterol 27-hydroxylase (CYP27A1) are essential regulators of cholesterol metabolism. However, their tissue-specific roles, particularly in the lung, under high-cholesterol diet (HCD) conditions remain unclear.ObjectiveUsing the liver as a reference, this study aimed to investigate the tissue-specific regulation of ABCA1 in the lung under HCD or CYP27A1 knockout (KO) conditions, and to explore its potential regulatory mechanism.MethodsCYP27A1 KO and wild-type (WT) mice on a C57BL/6J background were fed either a normal diet (ND) or HCD for 12 weeks. Transcriptome sequencing (RNA-seq) was conducted on lung tissue samples.ResultsHCD feeding in WT mice caused significant hepatic lipid accumulation, while no notable lipid deposition was observed in lung tissue. ABCA1 and CYP27A1 expression were downregulated in the liver but upregulated in the lung. In CYP27A1(−/−) mice, hepatic lipid accumulation was more severe with further suppression of ABCA1, whereas ABCA1 expression in the lung remained elevated. Transcriptome analysis revealed that upregulated genes in lung tissue were significantly enriched in the inflammation-related nuclear factor kappa-B (NF-κB) signaling pathway. Furthermore, experiments confirmed that the expression of NF-κB pathway was consistent with the upregulation of ABCA1.ConclusionABCA1 exhibits marked tissue specificity under HCD feeding or CYP27A1 KO conditions. In the liver, ABCA1 downregulation may exacerbate cholesterol metabolic imbalance, while its upregulation in the lung may play an important role in maintaining cholesterol homeostasis. Moreover, the increase in pulmonary ABCA1 expression in CYP27A1 KO mice may be associated with activation of the NF-κB signaling pathway.